Is seminal vesicle ablation mandatory for all patients undergoing radical prostatectomy? A multivariate analysis on 1283 patients - (:unkn) unknown (ELSEVIER SCIENCE BV, 2004)
Objective: With a shift in prostate cancer stage and a majority of patients operated nowadays with PSA levels <10 ng/ml, rates of seminal vesicle (SV) invasion found on radical prostatectomy specimens have decreased as compared to historical data. Since SV-sparing surgery may possibly have an influence on post-operative erectile dysfunction and urinary recovery, we tried to determine which patients could be safely spared SV excision during radical prostatectomy. Material and methods: We used preoperative data from 1283 patients operated by radical retropubic prostatectomy-777 with serum PSA <10.0 ng/ml-to predict SV invasion on final pathological examination. Variables analyzed included age, digital rectal examination, serum PSA, biopsy Gleason score and percentage of biopsy cores invaded by prostate cancer. Statistical analysis included univariate, multivariate logistic regression analysis and receiver operating characteristic (ROC) curves. Results: Out of 1283 patients, 137 (10.6%) had SV involvement, 41/777 (5.2%) with PSA<10.0 ng/ml, 16.1% in the 10-20 ng/ml range and 26.2% when PSA was >20 ng/ml. Percentage of biopsies affected by prostate cancer and biopsy Gleason score were significant predictors of SV invasion in multivariate analysis, both in the entire population and in the subset of patients with PSA <10.0 ng/ml (p < 0.0001). Probability graphs created for patients with PSA <10 ng/ml indicate a risk of seminal invasion <5% when Gleason score on biopsy is <7 or when the percentage of biopsies affected by cancer is <50%. Conclusions: Resection of SV might not be oncologically necessary in all patients undergoing RP when PSA levels are below 10 ng/ml except when biopsy Gleason score is greater than or equal to7 or when more than 50% of prostate biopsy cores show cancer involvement. SV-sparing surgery could be prospectively compared to standard retropubic prostatectomy in selected individuals analyzing potential benefits on erectile function and urinary continence. (C) 2004 Elsevier B.V All rights reserved.
Keywords: seminal vesicle; staging; radical prostatectomy; prostate specific antigen; RETROPUBIC PROSTATECTOMY; CANCER; INVASION; ADENOCARCINOMA; RESECTION; BIOPSIES; DISEASE; PLEXUS